Mafic Archean continental crust prohibited exhumation of orogenic UHP eclogite - Palin, R; Moore, J; Zhang, Z; Huang, G; Wade, J; Dyck, B (Elsevier, 2021)
The absence of ultrahigh pressure (UHP) orogenic eclogite in the geological record older than c. 0.6 Ga is problematic for evidence of subduction having begun on Earth during the Archean (4.0–2.5 Ga). Many eclogites in Phanerozoic and Proterozoic terranes occur as mafic boudins encased within low-density felsic crust, which provides positive buoyancy during subduction; however, recent geochemical proxy analysis shows that Archean continental crust was more mafic than previously thought, having greater proportions of basalt and komatiite than modern-day continents. Here, we show via petrological modelling that secular change in the petrology and bulk composition of upper continental crust would make Archean continental terranes negatively buoyant in the mantle before reaching UHP conditions. Subducted or delaminated Archean continental crust passes a point of no return during metamorphism in the mantle prior to the stabilization of coesite, while Proterozoic and Phanerozoic terranes remain positively buoyant at these depths. UHP orogenic eclogite may thus readily have formed on the Archean Earth, but could not have been exhumed, weakening arguments for a Neoproterozoic onset of subduction and plate tectonics. Further, isostatic balance calculations for more mafic Archean continents indicate that the early Earth was covered by a global ocean over 1 km deep, corroborating independent isotopic evidence for large-scale emergence of the continents no earlier than c. 3 Ga. Our findings thus weaken arguments that early life on Earth likely emerged in shallow subaerial ponds, and instead support hypotheses involving development at hydrothermal vents in the deep ocean.